Next generation of nanozymes: A perspective of the challenges to match biological performance - Goya, Gerardo Fabian (2021)
Nanomaterials with enzyme-like activity have been the spotlight of scientific and technological efforts to substitute natural enzymes, not only in biological research but also for industrial manufacturing, medicine, and environment healing. Notable advancements in this field along the last years relied on to the rational design of single-atom active sites, knowledge of the underlying atomic structure, and realistic ab initio theoretical models of the electronic configuration at the active site. Thus, it is plausible that a next generation of nanozymes still to come will show even improved catalytic efficiency and substrate specificity. However, the dynamic nature of the protein cage surrounding most active sites in biological enzymes adds a flexible functionality that possess a challenge for nanozyme's mimicking of their natural counterparts. We offer a perspective about where the main strategies to improve nanozymes are headed and identify some of the big challenges faced along the road to better performance. We also outline some of the most exciting bio-inspired ideas that could potentially change this field.